Comprehensive review & impact analysis of integrating projected electric vehicle charging load to the existing low voltage distribution system. (January 2022) - Rahman, Syed; Khan, Irfan Ahmed; Khan, Ashraf Ali; Mallik, Ayan; Nadeem, Muhammad Faisal
Abstract: Electric vehicles (EVs) have remarkably emerged as an alternative for internal combustion engines. With high penetration levels of the EVs, its addition to the existing distribution line infrastructure affects the power quality and grid stability. Additionally, EV charging loads are characteristically different as they are mobile compared to other fixed node-connected loads. Proposing solutions without considering these factors may result in grid congestion and subsequent over/under compensations. Another emerging dynamics co-occurring in the distribution system is high penetration levels of renewable energy in the utility grid. Although these dynamics pose challenges in stable grid operation, it also gives opportunities for solving some of the grid integration issues of EV loads. Thus, the effect of adding EV charging load to the existing low voltage distribution system must be analyzed by considering different criteria such as grid impact with different EV chargers, mobile nature of EV load, power quality, voltage profile, and spread/peak demand of load curve. This paper presents a detailed report on the impact analysis of EV integration on the component and system levels. For analyzing the effect on power quality (component level), grid pollution contributed by EV chargers along with possible solutions is elucidated. Detailed discussion on the significance of EV load location, existing load distribution, and nature of EV charging load distribution is presented by considering different feeders and different load curves. These discussions are supported with simulated case studies followed by a review of existing literature for enhanced understanding. Finally, techniques employed to effectively model the mobile nature of EV load and distributed EVs potential to provide ancillary solutions are also explained. Highlights: Simulation results of grid distortion by different EV loads are discussed. A detailed analysis of the impact of EV load on low-voltage distribution is presented. Review of EV load impact on different feeders' voltage profile is discussed. Probabilistic and stochastic model quantifying the EV load random are highlighted. Opportunities for solving grid issues with distributed EVs are summarized.